Treated rubberised engineered cementitious composites (ECC) for modern civil engineering material / Atiqah Abdul Aziz, Nor Asyiqin Jafri and Noorliyana Zakaria - Abdul Aziz, Atiqah; Jafri, Nor Asyiqin; Zakaria, Noorliyana (College of Built Environment, 2023)
Engineered cementitious composites (ECC) - Eexcellent mechanical qualities and permanence that has a lot of interest from researchers and engineers.